Implementation Of The Community Satisfaction Index (Ikm) Measurement At Muara Betung Village Office, Ulu Musi District, Empat Lawang Regency - Suradilaga, Nanda; Susanti, Neri; Febliansa, M Rahman (Utami Publisher, 2026)
The implementation of the Community Satisfaction Index (IKM) measurement plays an important role in helping public service officials identify aspects that need improvement to achieve more optimal service delivery. In this context, the study was conducted at the Muara Betung Village Office, Ulu Musi District, Empat Lawang Regency, focusing on analyzing the level of community satisfaction with the public services provided. This study aims to determine and analyze the level of the Community Satisfaction Index (IKM) in Muara Betung Village. The research method refers to the Community Satisfaction Survey (SKM) guidelines as regulated in the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017. The survey assesses nine service elements, namely: requirements, procedures, service completion time, fees/tariffs, product or service type, competence of service providers, behavior of service providers, facilities and infrastructure, and complaint and suggestion handling. Based on the analysis results, the Community Satisfaction Index score was 78.75, which falls under service quality category B (Good), as it lies within the conversion range of 76.61–88.30. The lowest score was found in the service completion time element, with an average score of 2.29, categorized as less satisfactory. Meanwhile, the highest score was obtained in the behavior of service providers element, with an average score of 3.35, categorized as Good. Overall, these results indicate that public service delivery at the Muara Betung Village Office has been carried out well, although improvements are still needed in the aspect of service completion time to further enhance community satisfaction.